Advancing economic sustainability in E7 economies: the impact of green finance, environmental benefits, and natural resource management - Dai, Xulong; Wu, Junyu; Fan, Suqing; Zhou, Yanqi (Frontiers in Environmental Science, 2025)
Green finance (GFN) plays a critical role in reducing greenhouse gas emissions and air pollution, serving as a key financial mechanism to promote green growth and economic sustainability (ESS). This paper explores how GFN, along with fintech (FNT), environmental benefits (ENB), urbanization (URB), and natural resource management (NRM), influences ESS in E7 countries from 2000 to 2022. While fintech’s rapid technological advancements offer significant economic potential, they also introduce increased complexity and systemic risks. Using rigorous methods such as method of moments quantile regression (MMQR) and Westerlund analysis, this study validates the relationships and heterogeneity among these variables through preliminary tests, including matrix correlation, cross-sectional dependence (CSD), slope heterogeneity (SH), and CIPS unit root tests. The findings indicate that GFN, ENB, and FNT positively contribute to ESS, while URB and NRM have an inverse relationship with ESS. These insights not only deepen our understanding of how ecological factors influence economic sustainability but also provide practical policy recommendations for E7 countries. The study’s conclusions offer valuable guidance for optimizing ESS and advancing toward sustainable development goals (SDGs).